A comparison of advertised versus actual cannabidiol (CBD) content of oils, aqueous tinctures, e-liquids and drinks purchased in the UK - Drusus A. Johnson; Megan Hogan; Ray Marriot; Liam M. Heaney; Stephen J. Bailey; Tom Clifford; Lewis J. James (BMC, 2023)
Abstract Background Cannabidiol (CBD)-containing products are sold widely in consumer stores, but concerns have been raised regarding their quality, with notable discrepancies between advertised and actual CBD content. Information is limited regarding how different types of CBD products may differ in their deviation from advertised CBD concentrations. Therefore, CBD concentrations were quantified and compared in aqueous tinctures, oils, e-liquids and drinks. Methods Products (13 aqueous tinctures, 29 oils, 10 e-liquids and 11 drinks) were purchased online in the UK. CBD concentrations were quantified in aqueous tinctures, oils and e-liquids via high performance liquid chromatography (HPLC), and in drinks via gas chromatograhy-mass spectrometry (GC-MS). Results Measured concentrations fell −25.7 ± 17.3, −6.1 ± 7.8, −6.9 ± 4.6 and − 0.03 ± 0.06 mg/mL below advertised concentrations for aqueous tinctures, oils, e-liquids and drinks, respectively (medians ± interquartile ranges; p < .05). Oils deviated relatively less (−19.0 ± 14.5%) from advertised concentrations than e-liquids (−29.2 ± 10.2%), aqueous tinctures (−51.4 ± 41.4%) and drinks (−65.6 ± 36.5%; p < .01), whilst e-liquids deviated less than aqueous tinctures and drinks (p < .05), and deviation was not different between aqueous tinctures and drinks (p = .19). Only 5/63 (8%) products had measured concentrations within 10% of advertised concentrations. Discussion Similarly to previous studies, few products had measured CBD concentrations within 10% of advertised concentrations, with most falling below advertised concentrations. All individual product types deviated from advertised concentrations, with oils deviating least. These findings may be indicative of poor manufacturing standards, or that CBD undergoes degradation in consumer products. This reinforces concerns over quality of CBD-containing consumer products and may highlight the need for improved regulation of such products.